Pomladitvena ekologija drugotnih visokogorskih smrekovih gozdov v Jelendolu - Rozman, Elizabeta (Zbornik gozdarstva in lesarstva, 2008)
Natural regeneration of altimontane spruce forests at Jelendol is retarded dueto many factors. In autumn 2003, gaps of different size and parts of the surrounding stand were covered with a 5 x 5 grid m to define sampling plots. Atotal of 227 plots with 1,5 x 1,5 m in size were installed to analyse generalregeneration conditions and inhibitors. The following ecological parameters were estimated on each plot: micro relief, inclination, soil depth,ground cover, direct and diffuse solar radiation. Woody regeneration (density, height, height increment) and ground vegetation were recorded at each plot. Considering that N-S and E-W radiation asymmetry was explicit, the distribution of direct and diffuse radiation was divided into four groups among the plots. Spruce regeneration (28.,605 per ha) was mainly found at the edge of the large gap, though total regeneration density and radiation were not correlated. However, in both the stand and the small gaps, the lack of radiation hindered further development. This study showed that light conditions were not the only factors affecting the regeneration success at an altitude of 1,500 m. The presence of woody debris was important, while the influence of the herb layer (predominant species were Festuca altissima All. and Calamagrostis arundinacea (L.) Roth.) and soil depth proved to be negative. The impact of browsing, however, remained the main problem.
Keywords: ekološki dejavniki; Jeledol; pomlajevanje; smrekovi gozdovi